Transfer of innovation on allergic rhinitis and asthma multimorbidity in the elderly (MACVIA-ARIA) Reference Site Twinning (EIP on AHA) : European Innovation Partnership on Active and Healthy Ageing GARD research demonstration project - Bousquet, Jean (2018)
Transfer of innovation on allergic rhinitis and asthma multimorbidity in the elderly (MACVIA-ARIA) - EIP on AHA Twinning Reference Site (GARD research demonstration project)